2012
DOI: 10.4103/1735-3327.104882
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the bactericidal efficacy of photodynamic therapy, 2.5% sodium hypochlorite, and 2% chlorhexidine against Enterococcous faecalis in root canals; an in vitro study

Abstract: Background:Enterococcus faecalis has been widely used as a valuable microbiological pathogen for in vitro studies due to its ability to successfully colonize the root canal in a biofilm-like style, invade dentinal tubules, and resist endodontic treatment procedures.The aim of this study was to compare the bactericidal efficacy of photodynamic therapy (PDT), 2% chlorhexidine, 2.5% NaOCl, and combination of PDT and 2.5% NaOCl against E. faecalis.Materials and Methods:Sixty single-rooted teeth had their canals co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 38 publications
(79 reference statements)
1
47
1
1
Order By: Relevance
“…With regard to the effect of PDT in reducing E. faecalis, some studies found it less effective than NaOCl (25,(29)(30)(31)37), others found them similarly effective (34,35), and others found that PDT had better results when associated with NaOCl (27,29,31,33,37).…”
Section: Pdt Parametersmentioning
confidence: 99%
See 4 more Smart Citations
“…With regard to the effect of PDT in reducing E. faecalis, some studies found it less effective than NaOCl (25,(29)(30)(31)37), others found them similarly effective (34,35), and others found that PDT had better results when associated with NaOCl (27,29,31,33,37).…”
Section: Pdt Parametersmentioning
confidence: 99%
“…Each article assessed in the present study had included a parameter for performing PDT, as summarized in Table 4. The use of intracanal fiber was not universal, since Vaziri et al (31) did not describe its use.…”
Section: Pdt Parametersmentioning
confidence: 99%
See 3 more Smart Citations